Encephalitozoonosis in 2 South American Fur Seal (Arctocephalus australis) Pups. (July 2015) - Seguel, M.; Howerth, E. W.; Ritter, J.; Paredes, E.; Colegrove, K.; Gottdenker, N.
Cerebral and disseminated encephalitozoonosis was diagnosed by histopathology, electron microscopy, and immunohistochemistry in 2 free-ranging South American fur seal pups found dead at Guafo Island (43°33′S 74°49′W) in southern Chile. In the brain, lesions were characterized by random foci of necrosis with large numbers of macrophages containing numerous microsporidial organisms within parasitophorous vacuoles. In addition, occasional histiocytes loaded with numerous mature and immature microsporidia spores consistent with Encephalitozoon sp were observed in pulmonary alveolar septa, splenic red pulp, glomerular capillaries, and proximal renal tubules by Gram and immunohistochemical stains. To our knowledge, microsporidial infection in a marine mammal species has not been previously reported.